REVASCULARIZACIÓN EN DIENTE PERMANENTE INMADURO CON PERIODONTITIS APICAL USANDO NEOPUTTY MTA. REPORTE DE CASO - Cordido Useche, Aleska Irina (2025)
The treatment of young necrotic permanent teeth with open apices represents a challenge for endodontists. Revascularization has emerged as a biologically based treatment alternative that allows the continued development of immature teeth. This procedure requires a hermetic coronal seal with a biocompatible cement. The objective of this work is to present a case of revascularization of an immature tooth with open apices in a 7-year-old patient, in Cvek stage III, with the diagnosis of previously initiated therapy and asymptomatic apical periodontitis, using NeoPUTTY MTA as a cervical barrier. After informed consent, the protocol proposed by Wei was followed in 2 appointments; using calcium hydroxide as intracanal medication in the first appointment, and performing the apical puncture in the second appointment, after an irrigation protocol with passive ultrasonic activation. The cervical barrier was created by compacting NeoPUTTY MTA and covered with TheraCal LC plus glass ionomer and composite resin. The patient was evaluated in 4 post-treatment consultations, at 3 weeks, 6 weeks, 6 months and 1 year; he remained asymptomatic throughout the process and presented progressive radiographic improvement until resolution of the apical lesion, increased thickness of the root walls, decreased apical diameter of the mesial root to approximately 0.5 mm and of the distal root to approximately 1 mm and the formation of a new periodontal ligament space.